Modeling and forecasting exchange rate volatility: comparison between EEC and Developed countries - Miletić, Siniša (Industrija, 2015)
The main objective of this study is to test the hypothesis that exchange rates in emerging countries are more sensitive to negative shocks than positive ones, and that developed ones do not exhibit this same pattern, at least not with the same intensity. In order to measure the involved risk, symmetric and asymmetric GARCH models are applied. The accuracy of exchange rate volatility forecast is evaluated using the Mincer-Zarnowitz regression based test and Diebold and Mariano test (DM test). The daily exchange rate returns of HUF/USD, RON/USD and RSD/USD for EEC countries and, the EUR/USD, GBP/USF and JPY/USD for developed countries are analysed for the period January 3, 2000 to April 15, 2013, in respect. Estimation results confirmed superiority of GARCH model in comparison to asymmetric GARCH models. Results of predictability of conditional variance indicate that GARCH model offers superior performance of forecasting in both of EEC and developed countries. Only in case of Romanian lei TGARCH outperformed GARCH model.
Keywords: Diebold and Mariano test (DM test); Mincer-Zarnowitz regression based test; Developed countries; EEC countries; GARCH models; Volatility; Exchange rate